Influence of the nitrogen pots from graphitic carbon nitride with the presence of wrinkled silica-titania for photodegradation enhancement of 2-chlorophenol. (26th February 2023) - Azami, M.S.; Jalil, A.A.; Aziz, F.F.A.; Hassan, N.S.; Mamat, C.R.; Izzudin, N.M.
Abstract: An interlayer structure hybrid wrinkled silica titania (WST) loaded on graphitic carbon nitride (g-C3 N4 ) was successfully constructed using facile microwave-assisted solid-state technique. The as-prepared materials were characterized using N2 adsorption-desorption, XRD, FESEM, UV–Vis DRS, FTIR, and TEM analysis. The photocatalytic degradation of 2-chlorophenol (2-CP) towards visible light illumination (150 mW/cm 2 ) is following the sequence: 10 wt% WST@CN (91%) > 5 wt% WST@CN (65%) > g-C3 N4 (63%) > 15 wt% WST@CN (58%) ˃ WST (50%). The supreme photocatalytic performance of 10 wt% WST@CN was owing to the WST morphology that more concealed between stacked layer of g-C3 N4, as a consequence of the stronger interaction between "nitrogen pots" of the g-C3 N4 and Si/Ti species of the 10 wt% WST, and thus, enhanced the efficiency of charge separation. These criteria provide better charge carrier mobility for enhanced visible light driven photocatalytic performance. The kinetic studies revealed that the photocatalytic degradation of 2-CP using 10 wt% WST@CN obeyed a model of pseudo-first order, with the surface reaction being the rate determining step. Subsequently, the scavenger study confirmed that hydroxyl radicals that absorbed on the catalyst surface play a major role over 10 wt% WST@CN as emerged from the mechanism of Z-scheme. It is notable that the interfacial of WST@CN composite could appear as an excellent catalyst for its useful application for endocrine disruptive wastewater treatment. Graphical abstract: Image 1 Highlights: WST@CN composites were synthesized via microwave-assisted solid-state method. 10 WST@CN shows the highest photodegradation of 2-CP (91%). The dendrimer morphology of WST was concealed on the stacked layer of g-C3 N4 . 10 WST@CN possesses the strong interaction between nitrogen pots and Si/Ti. Z-scheme has preserved the strong redox potential for enhancement of performance.